Large-scale genome-wide association study to identify causal relationships and potential mediators between education and autoimmune diseases - Li, Yingjie; Zhang, Jingwei; Wen, Jie; Liu, Mingren; Liu, Wanyao; Li, Yongzhen (Frontiers in Immunology, 2023)
Objectives: Epidemiological studies suggested a potential connection between education and autoimmune disorders. This study investigated the possible cause-and-effect relationship using a Mendelian randomization approach. Methods: We explored the causality between four education traits (n = 257,841 1,131,881) and 22 autoimmune diseases. The mediating role of smoking (632,802 individuals), BMI (681,275 individuals), alcohol (335,394 individuals), and income (397,751 individuals) was also investigated. Transcriptome-wide association study (TWAS) and enriched signaling pathways analysis were used to investigate the underlying biological mechanisms. Results: Especially, higher cognitive performance was protective for psoriasis (odds ratio (OR) = 0.69, 95% confidence interval (CI) = 0.60-0.79, p = 6.1210-8), rheumatoid arthritis (RA) (OR = 0.75, 95% CI = 0.67-0.83, p = 4.6210-6), and hypothyroidism (OR = 0.83, 95% CI = 0.77-0.90, p = 9.8210-6). Higher levels of educational attainment decreased risks of psoriasis (OR = 0.61, 95% CI = 0.52-0.72, p = 1.1210-9), RA (OR = 0.68, 95% CI = 0.59-0.79, p = 1.5610-7), and hypothyroidism (OR = 0.80, 95% CI = 0.72-0.88, p = 5.0010-6). The completion of highest-level math class genetically downregulates the incidence of psoriasis (OR = 0.66, 95% CI = 0.58-0.76, p = 2.4710-9), RA (OR = 0.71, 95% CI = 0.63-0.81, p = 5.2810-8), and hypothyroidism (OR = 0.85, 95% CI = 0.79-0.92, p = 8.8810-5). Higher self-reported math ability showed protective effects on Crohn's disease (CD) (OR = 0.67, 95% CI = 0.55-0.81, p = 4.9610-5), RA (OR = 0.76, 95% CI = 0.67-0.87, p = 5.2110-5), and psoriasis (OR = 0.76, 95% CI = 0.65-0.88, p = 4.0810-4). Protein modification and localization, response to arsenic-containing substances may participate in the genetic association of cognitive performance on UC, RA, psoriasis, and hypothyroidism. According to mediation analyses, BMI, smoking, and income serve as significant mediators in the causal connection between educational traits and autoimmune diseases. Conclusion: Higher levels of education-related factors have a protective effect on the risk of several autoimmune disorders. Reducing smoking and BMI and promoting income equality can mitigate health risks associated with low education levels.